Theoretical Perspectives of Occupational Health Nurses (OHN) career in Indonesia - Syaifoel Hardy; Isak JH Tukayo; Ridha Afzal; Noor Hadi (Universitas Muhammadiyah Surakarta, 2021)
Background: According to the Central Statistics Agency (BPS, 2020), the number of medium-large industries in 2019 in Indonesia 30,381. This number is followed by the growth in healthcare services, which is classified as the highest among 17 existing sectors (Databoks, 2020). These opportunities and challenges prove that from the OHN employment perspective, the prospects for the OHN professionals are very promising. In terms of education where nursing specialization in Indonesia is still very limited, the career of the OHN corporate nursing profession needs to be analyzed and explored.Purposes: This review aims to enhance the understanding of OH nurses' careers in an increasingly dynamic educational environment, provides comprehensive understanding of the world of work for OHN nurses, and offers future research direction.Method: The methods used was to review three career model Career Framework, Change Model by Kotter and comparing with the competency-based by Delphi Model and Quinn Model. The results of the analysis and exploration were applied with a review of the nursing education system by the Ministry of Health, the National Education System, Ministry of Higher Education (Ristekdikti), Development and Empowerment of Healthcare Human Recources (BPPSDM), OHN Career Guide Canada and several journals of the last five years, from 2016 to 2020.Result: The review shows there is significant relationship between nursing education career paths in Indonesia and the flow and structure recommended by the three models in general nursing career, not specifically in the OHN perspectives.